Obstacle Avoidance amongst Parkinson Disease Patients Is Challenged in a Threatening Context. (15th May 2013) - Doan, Jon B.; de Bruin, Natalie; Pellis, Sergio M.; Suchowersky, Oksana; Whishaw, Ian Q.; Brown, Lesley A.
Abstract : We examined whether people with Parkinson disease (PD) have difficulty negotiating a gait obstruction in threatening (gait path and obstacle raised above floor) and nonthreatening (gait path and obstacle at floor level) contexts. Ten PD patients were tested in both Meds OFF and Meds ON states, along with 10 age-matched controls. Participants completed 18 gait trials, walking 4.7 m at a self-selected speed while attempting to cross an obstacle 0.15 m in height placed near the centre point of the walkway. Kinematic and kinetic parameters were measured, and obstacle contact errors were tallied. Results indicated that PD patients made more obstacle contacts than control participants in the threatening context. Successful crossings by PD patients in the threatening condition also exhibited kinematic differences, with Meds OFF PD patients making shorter crossing steps, with decreased initiation and crossing velocities. The findings from this study lend support to the theory that PD patients rely on directed attention to initiate and control movement, while providing indication that the motor improvements provided by current PD pharmacotherapy may be limited by contextual interference. These movement patterns may be placing PD patients at risk of obstacle contact and falling.